Strategi Kepemimpinan Kepala Sekolah dalam Mengembangkan Sumber Daya Manusia pada Abad 21 - Muhammad Hulkin; Zulhijrah Zulhijrah; Sinta Bella; Shaleh Shaleh (Ideguru: Jurnal Karya Ilmiah Guru, 2024)
Leadership is one of the most important components to keep an organization running. Every organization has a leader in order to run the organization. This study aims to analyze the principal's leadership strategy in developing human resources in the 21st century, focusing on the principal's role in facing the challenges of globalization and improving teacher professionalism and technology-based teaching. This research uses a descriptive qualitative approach method. The data collection technique used interview technique. This research was conducted at Fathona Pakjo Integrated Islamic Elementary School in Palembang. The results of this study indicate that the principal's leadership strategy is very important for the development of human resources in schools, namely conducting training for teachers in order to develop human resources in schools collaborative work environment, and focus on developing students' skills, ethics, and social responsibility. The implication of this study is that principals need to take a more progressive, inclusive and collaboration-oriented leadership approach to ensure that human resources in schools can face global challenges effectively.